2010
DOI: 10.1016/j.envpol.2009.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of mercury fluxes and their controlling factors in large Hg-polluted floodplain areas

Abstract: Dynamics of mercury fluxes and their controlling factors in large Hg-polluted floodplain areas.Environmental Pollution, 158, 308-318.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 48 publications
0
28
0
1
Order By: Relevance
“…In addition, Hg may enter the foliage by recycling processes, releasing GEM from underlying soil surfaces (Millhollen et al, 2006b). Soil-air GEM exchange is controlled by numerous factors, including physicochemical properties of soil substrate and abiotic/biotic processes in the soil, meteorological conditions, and atmospheric composition (Bahlmann et al, 2006;Carpi and Lindberg, 1997;Engle et al, 2005;Fritsche et al, 2008a;Gustin, 2011;Rinklebe et al, 2010;Mauclair et al, 2008;Zhang et al, 2008). The majority of reported GEM flux measurements over terrestrial soils have indicated net emission in warmer seasons and near-zero fluxes in cold temperatures (Sommar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Hg may enter the foliage by recycling processes, releasing GEM from underlying soil surfaces (Millhollen et al, 2006b). Soil-air GEM exchange is controlled by numerous factors, including physicochemical properties of soil substrate and abiotic/biotic processes in the soil, meteorological conditions, and atmospheric composition (Bahlmann et al, 2006;Carpi and Lindberg, 1997;Engle et al, 2005;Fritsche et al, 2008a;Gustin, 2011;Rinklebe et al, 2010;Mauclair et al, 2008;Zhang et al, 2008). The majority of reported GEM flux measurements over terrestrial soils have indicated net emission in warmer seasons and near-zero fluxes in cold temperatures (Sommar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our funnels were installed several weeks before making any measurements in order to minimize this disturbance. However, the alternative was to remove a large volume of soil and measure TGM concentrations in a controlled environment similar to the technique used in Rinklebe et al 2010 and many others. The removal technique also has several limitations which were unacceptable from our perspective.…”
Section: Concern 6: Inserting the Funnel Top Down And Then Replacing mentioning
confidence: 99%
“…The dataset was collected during seven sampling campaigns, which contained all seasons. Soil microcosm experiments under definite temperature and soil water conditions were carried out to study the impact of the main controlling factors on Hg emission from the soils (Rinklebe et al, 2009;2010). To measure TGM emissions, the system described by Rinklebe et al (2009), modified from Böhme et al (2005), was used.…”
Section: Methodsmentioning
confidence: 99%
“…One example is the Elbe River in Germany and its catchment areas; large amounts of heavy metals including Hg from a range of anthropogenic and geogenic sources have been accumulated in the soils of these floodplains (Rinklebe et al, 2009(Rinklebe et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation